The return of the common good : the postliberal project left and right - Borg, Stefan (Routledge, 2026)
In this book, Stefan Borg reconstructs and engages a contemporary strand of thought known as postliberalism. Postliberalism, Borg argues, advances a distinct critique of liberalism, as well as an emphasis on the common good as a corrective to the perceived shortcomings of liberalism. The central claim is that the two dominant forms of post-World War II liberalism, market liberalism and social liberalism, rather than being somehow opposed, have coalesced around a political project that above all seeks to maximize the conditions under which individual autonomy can be exercised. As a result, the liberal sociopolitical order has become increasingly inept at nurturing the communal resources that underpin human sociability.A work of contemporary intellectual history, Borg re-creates the birth of postliberalism, compares both British and American strands of postliberal thinking and reconstructs postliberalism across disciplines. In addition, Borg argues that while the postliberal critique resonates with segments on the political Right as well as the Left, postliberal prescriptions, which revolve around the promotion of the common good, are more controversial.Engaging and thought-provoking, The Return of the Common Good: The Postliberal Project Left and Right is suitable for a broad set of readers and an invaluable guide to further debates on liberalism and populism.
Keywords: Liberalism -- Great Britain -- History -- 21st century.; Liberalism -- United States -- History -- 21st century.; Populism -- Great Britain -- History -- 21st century.; Populism -- United States -- History -- 21st century.; elektronické knihy; electronic books